Women rough sleepers in Europe : homelessness and victims of domestic abuse - Moss, Kate, 1965-; Singh, Paramjit, 1971- (Bristol : Policy Press, 2015)
This important book reveals a number of truths about women's rough sleeping across Europe and argues for the adoption of effective policy, strategies and services to meet the needs of homeless women, and specifically women rough sleepers who are the victims of domestic abuse.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Homeless women -- Europe; Victims of family violence; Abused women